Effect of heat and ultrasonic-assisted extraction on nutritional characteristics, functional properties, and bioactivities of tuna liver protein concentrate powders - Thunnipa Chueadoem; Chakkapat Aenglong; Lalitphan Kitsanayanyong; Wanwimol Klaypradit; Pramvadee Tepwong (Journal of Agriculture and Food Research)
Skipjack tuna (Katsuwonus pelamis) liver (TL), an underutilized by-product of the canned tuna industry, is typically used for the animal feed industry. To enhance the high-value utilization of TL, this study investigated the influence of green extraction methods, including heat extraction at 85 °C assisted by ultrasonic bath at 40 kHz (HUB40) or 80 kHz (HUB80), and ultrasonic probe at 40 % (HUP40) or 60 % (HUP60) amplitude, for 30 or 45 min. The results indicated that HUB80 and HUP60 extraction for 30 min yielded the highest protein recovery and were selected for subsequent drying (hot air drying, HD; vacuum drying, VD; freeze drying, FD) to produce tuna liver protein concentrates (TLPC) powders. The results showed that all TLPC powders contained high protein content and retained amino acid profiles comparable to TL powders, with glutamic acid, aspartic acid, and leucine as dominant amino acids. While SDS-PAGE confirmed unchanged primary structure, FTIR revealed secondary structural shifts, wherein reduced α-helix and increased β-sheet content. In addition, HUP60 and HUB80 improved foaming and emulsifying properties under all drying methods. Additionally, TLPC powders produced using HUB80 and HUP60 with FD showed improved DPPH and ACE inhibitory activities, while VD enhanced ABTS and FRAP values. In contrast, heat extraction alone (H85) followed by drying resulted in greater Fe2+ chelating ability. These findings suggest that ultrasonic-assisted extraction combined with suitable drying methods could improve the nutritional and functional potential of TLPC for application in foods.